BURNOUT SYNDROME IN ATHLETES - Trifković, Nada (Sport - nauka i praksa, 2023)
Burnout syndrome is a consequence of accumulated stress, caused by excessive engagement, both in the physical and mental (psychological) domains. It is characteristic of many professions, especially professions that involve direct work with people (healthcare, education, army, etc.), and in sports it is almost inevitable. The two most common reasons that cause burnout syndrome are: setting hard-to-achieve goals or unrealistic deadlines and trying to meet other people’s (imposed) expectations. In both cases, endurance limits are pushed, which leads to burnout and has consequences for the entire human body and psychophysical health. We live in a harsh age where it is not enough to be successful, the demand is to be the best. This ultimatum is particularly prominent in sports. Athletes are distinguished from others by discipline, perseverance, persistence, focus on the goal (victory), sacrifice and responsibility. Top fitness and top results are always expected from them. The question arises: Is it even possible to achieve top results and avoid the burnout syndrome? In addition to the analysis of causes, symptoms and consequences, the paper seeks an answer to this question.